Efektifitas Program Sosialisasi Bahaya Narkoba Dalam Mencegah Penyalahgunaan Narkoba Terhadap Remaja di Kabupaten Bireuen - MY, M. Yusuf; Zabir, Muzakkir (Yayasan Madinah Al-Aziziyah, 2023)
Drug abuse is an issue of great concern. Actually, if not abused, drug ingredients are useful, both for health and daily life. However, the use of these drugs must be based on the dosage and uses that can only be prescribed by experienced experts such as doctors and pharmacists. Drug abuse cases handled by Bireuen Police in 2016 continued to increase sharply compared to 2015. A total of 81 cases with evidence of six marijuana sticks (samples) and 1,021.96 grams of methamphetamine and 149 suspects, while methamphetamine cases amounted to 6,408.66 grams and involved 122 suspects, 107 suspects stumbled upon methamphetamine cases, this condition continues to increase every year. Currently (2020) in Bireuen Regency, drug problems are rampant, as is the case in Peusangan, drug use is not only among male teenagers but also used by female teenagers, the type of drug used is ngelem. The purpose of this research is to find out the efforts made by BNN Bireuen Regency in counseling the dangers of drugs to adolescents and to find factors of opportunities and challenges faced by BNN in counseling the dangers of drugs in Bireuen Regency. The method in this research is field research, data collection techniques with observation interviews and documentation. The results showed that BNN Kabupeten Bireuen has carried out activities well, such as P4GN activities and anti-drug task force activities as well as the formation of drug-free gampong. While the opportunity is the support of the central BNN as well as good cooperation between stakeholders and also the expectations of the community, while the challenge is the terror carried out by drug dealers, as well as the lack of budget for each activity and the lack of medical equipment.